Diplomasi Ekonomi Indonesia dan Thailand terhadap Pasar Timur Tengah - Kurniawan, Andi (Jurnal Ilmu Sosial dan Ilmu Politik, 2014)
Economic diplomacy as an instrument has been employed by Thailand to boost its export performance to partner countries, including to the Middle East region. Unlike Thailand, Indonesia the regionâs largest Moslem country remains unable to capitalize on friendly relation with Middle East to boost its foreign trade. This study brought these facts into a research aimed at enriching the literatures of Indonesiaâs economic relations with Middle East. Research method used in the study was qualitative approach. It concluded that despite cultural differences, Thailand is relatively successful in conducting economic diplomacy to promote its top commodities to this market.